St. John’s wort treatment in women bears risks beyond pharmacokinetic drug interactions - Hohmann, Nicolas; Maus, Anna Sabina; Carls, Alexandra; Haefeli, Walter E.; Mikus, Gerd (Archives of toxicology, 2016)
We analyzed adverse events in a clinical phase I trial to assess dose-dependent metabolic effects of St. John’s wort co-administered with rifampicin in 12 healthy volunteers. Within 3-6 days after increasing the St. John’s wort dose from 300 to 600 mg TID, five of six female participants developed ambient temperature-dependent allodynia and paresthesia in sun-exposed areas (back of the hands and perioral and nasal area). Aggravation of symptoms resulted in persistence of paresthesia and phototoxic erythrodermia. None of the male participants showed any of these effects. Gender, duration of treatment, dose, and solar exposure seem to be extrinsic and host factors facilitating St. John’s wort-induced neuropathy. The risk to develop this adverse effect is almost exclusively present in women.
Published online: 12 May 2015
Gesehen am 06.02.2020